Connecticut Birding Guide. - Sabbatical Report - Smith, Dwight R. (1996)
Keywords: dept.bio; faculty_collection; sabbatical_report

Habitat and spatial relationships of nesting Swainson's Hawks (Buteo swainsoni) and red-tailed hawks (B. jamaicensis) in northern Utah - Bosakowski, T.; Kamsey, R.D.; Smith, D.G. (Great Basin Naturalist, 1996)
A total of 28 Swainson's Hawk (Buteo swainsoni) and 30 Red-tailed Hawk (B. jamaicensis) nests were found in Cache Valley. Utah, during the summers of 1992 and 1993. All nests were in trees, but only Red-tailed Hawks nested in dead trees (30%). In the intensive study area, nesting densities were 0.10 nests/km2 for Swainson's Hawk and 0.08 nests/km2 for Red-tailed Hawk. Nearest-neighbor nest distances were significantly shorter among Swainson's Hawks (1.74 km) than among Red-tailed Hawks (2.83 km). Congeneric nearest- neighbor distances were significantly shorter than conspecific distances for Red-tailed Hawks (1.59 vs. 2.83 km) but not for Swainson's Hawks (1.52 vs. 1.74 km). GIS analysis of habitat types was made for 2-km radii around nest sites. Cropland was the dominant land cover type of nest sites of both species and no significant difference was found between species. Swainson's Hawk nest sites contained significantly more pasture, whereas Red-tailed nest sites contained significantly more juniper, maple, and sagebrush. Only Red- tailed Hawk nests (n=8; 27%) were found on the periphery of the valley at the base of foothills of the Cache Mountains. This preference resulted in a significantly higher elevation for Red-tailed Hawk nest sites. Swainson's Hawk nests occurred only on the valley floor on level terrain. Distance to the nearest paved road and building was very similar for both species, implying that little difference exists in tolerance levels for human activities. Overall, multivariate niche overlap for habitat was high (0.89), indicating a lack of habitat partitioning between these 2 Buteos in Cache Valley.
Keywords: Buteo; Buteo jamaicensis; Buteo swainsoni; GIS; Red-tailed Hawk; Swainson's Hawk; dept.bio; habitat; nest sites; ⛔ No DOI found

Group hunting forays of wintering Northern Harriers, Circus cyaneus: An adaption of juveniles? - Bosakowski, T.; Smith, D.G. (Canadian Field-Naturalist, 1996)
The social interactions of a wintering population of Northern Harriers (Circus cyaneus) were studied in the Hackensack Meadowlands tidal marshes in New Jersey. Juvenile harriers were numerically dominant in the population and participated in hunting groups significantly more often than adult males or females. Group sizes varied from 2-4 birds (total groups observed = 66 duets, five trios and two quartets). The occasional inclusion of adults in a foraging group was usually the result of juveniles following the adult, presumably for the parasitic benefits of grabbing flushed prey or exploiting high yield foraging patches. Our observations suggested a non-territorial wintering harrier population documented by observations of 3-6 different individuals frequently hunting the same 12-ha area each day as well as random use of our study quadrats (3-ha) by individuals of all sexes and ages. Territorial defense was observed in only one adult female, which infrequently attempted to defend a territory. Overall, the prevalence of group-foraging behavior is consistent with the general lack of winter territory in this population.
Keywords: Circus cyaneus; Hackensack Meadowlands; New Jersey; Northern Harrier; dept.bio; following; foraging; group hunting; winter ecology; ⛔ No DOI found